Efficient and Tunable 1.6-μm MgO:PPLN Optical Parametric Oscillator Pumped by Nd:YVO4/YVO4 Raman Laser - Lei Zhao; Xin Ding; Jian Liu; Guizhong Zhang; Xuanyi Yu; Yang Liu; Bing Sun; Jingbo Wang; Yuntao Bai; Guoxin Jiang; Peng Lei; Tengteng Li; et al. (IEEE Photonics Journal, 2020)
A highly-efficient tunable 1.6 μm MgO:PPLN-OPO, which we believe to be the first one pumped by a diode-end-pumped Raman laser, is demonstrated. A good beam-quality of actively Q-switched Nd:YVO4/YVO4 Raman laser at 1176 nm and a good mode matching of the whole system resulted in a high-performance OPO. The highest Raman-to-signal conversion efficiency was 49.5% at 1638.8 nm when the incident Raman power was 2 W. The maximum output power of 3.2 W at 1663.5 nm with the pulse-width of 2.85 ns was obtained pumped by 7.57-W Raman laser. Meanwhile, the linewidth was less than 0.3 nm and a high beam quality with M2 factor of 1.92 was obtained.